The syncretic project management model in BANI environment - Sergiy Bushuyev; Andrii Ivko; Oleh Ilin (Scientific Results, 2024)
The syncretic project management model offers a novel approach to navigating the complexities of contemporary project environments, particularly those characterized by BANI (Brittle, Anxious, Nonlinear, Incomprehensible) conditions. By integrating interdisciplinary collaboration, agile methodologies, and artificial intelligence, this model seeks to enhance project resilience, adaptability, and innovation. This research explores the theoretical underpinnings of syncretic project management, examining its core components and the mechanisms through which it addresses the challenges posed by BANI environments. The study contributes to the evolving body of knowledge on project management by providing a comprehensive framework that can be applied across various industries and project contexts. This paper proposes a mathematical framework using category theory to maintain consistency between various system engineering models, improving the relevance of analyses in critical systems. In recent decades, there has been a significant increase in systems’ complexity, leading to a rise in the need for more and more models. Models created with different intents are written using different formalisms and give diverse system representations